2012
DOI: 10.1111/j.1442-9993.2012.02392.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐fire regeneration in alpine heathland: Does fire severity matter?

Abstract: Fire severity is thought to be an important determinant of landscape patterns of post-fire regeneration, yet there have been few studies of the effects of variation in fire severity at landscape scales on floristic diversity and composition, and none within alpine vegetation. Understanding how fire severity affects alpine vegetation is important because fire is relatively infrequent in alpine environments. Globally, alpine ecosystems are at risk from climate change, which, in addition to warming, is likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…It can be measured in the field or from remote sensing using multi-spectral indices that describe blackening (Hammill and Bradstock 2006). Also, studies have found that high-severity fires often have minimal effects on vegetation diversity, including in North American pine forests and west coast shrublands (Turner et al 1999, Purdon et al 2004, Keeley et al 2008, Fornwalt and Kaufmann 2014 and Australian eucalypt forests (Bradstock 2009, Knox and Clarke 2012, Camac et al 2013, Clarke et al 2014. However, there is increasing evidence that some floristic elements are favored by high-severity fires because these fires are required to trigger seed germination (Ooi et al 2006, Liyanage andOoi 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be measured in the field or from remote sensing using multi-spectral indices that describe blackening (Hammill and Bradstock 2006). Also, studies have found that high-severity fires often have minimal effects on vegetation diversity, including in North American pine forests and west coast shrublands (Turner et al 1999, Purdon et al 2004, Keeley et al 2008, Fornwalt and Kaufmann 2014 and Australian eucalypt forests (Bradstock 2009, Knox and Clarke 2012, Camac et al 2013, Clarke et al 2014. However, there is increasing evidence that some floristic elements are favored by high-severity fires because these fires are required to trigger seed germination (Ooi et al 2006, Liyanage andOoi 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is increasing evidence that some floristic elements are favored by high-severity fires because these fires are required to trigger seed germination (Ooi et al 2006, Liyanage andOoi 2015). Also, studies have found that high-severity fires often have minimal effects on vegetation diversity, including in North American pine forests and west coast shrublands (Turner et al 1999, Purdon et al 2004, Keeley et al 2008, Fornwalt and Kaufmann 2014 and Australian eucalypt forests (Bradstock 2009, Knox and Clarke 2012, Camac et al 2013, Clarke et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Small black dots represent important species. by promoting supervised natural succession (Maguire and Menges 2011;Camac et al 2013). Thus, on substrates that are unfavourable for rapid vegetation recovery after fire (like schist-derived soils in our test region), post-fire management of burnt areas may have to include active protection of soil against erosion as well as active plantation or seeding (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of post‐fire succession have primarily concentrated on the direct impacts of fire on forest recovery and linked those impacts to factors such as disturbance history, the regional species pool and species life histories (Girard, De Grandpré, & Ruel, ; Schoennagel, Veblen, & Romme, ). However, the specific role of biotic and abiotic factors in post‐fire regeneration can differ substantially among fires (Ackerly, ; Camac, Williams, Wahren, Morris, & Morgan, ; Nuñez & Raffaele, ), depending on the context provided by the characteristics of the local environment. Under certain unique geographical conditions, succession cannot be completely described by a general pattern of community development, but rather is the result of a variety of dynamic site‐specific factors that change the trajectory from the typical chronosequence (Conway & Johnstone, ; Yuan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of post-fire succession have primarily concentrated on the direct impacts of fire on forest recovery and linked those impacts to factors such as disturbance history, the regional species pool and species life histories (Girard, De Grandpré, & Ruel, 2014;Schoennagel, Veblen, & Romme, 2004). However, the specific role of biotic and abiotic factors in post-fire regeneration can differ substantially among fires (Ackerly, 2004;Camac, Williams, Wahren, Morris, & Morgan, 2013;Nuñez & Raffaele, 2007), depending on the context provided by the characteristics of the local environment.…”
Section: Introductionmentioning
confidence: 99%